Strengthening Religious Moderation for Ex-Terrorists through Islamic Education: Learning from the Yayasan Lingkar Perdamaian, Lamongan - Hepi Ikmal; Maskuri Maskuri; Dahlan Tamrin (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
This study aims to reveal how the Yayasan Lingkar Perdamaian (YLP) fosters former terrorists so that they can change or at least not commit violence and acts of terrorism in the name of religion. Through qualitative research, data was collected using in-depth interviews and observations of social activities in the field. The results of this study would like to suggest that strengthening religious moderation in former terrorist actors must be carried out in teaching-based Islamic education and social and psychological-based educational efforts. This means that the moderate character of ex-terrorists must be encouraged by various approaches that can open their hearts. So that they are willing to accept mistakes for their past behavior and are optimistic that they can socialize more with others based on Islamic educational values. Thus, Islamic education that is oriented towards a moderate religious understanding of terrorists must rely on rationalist and social aspects in a more humanist frame.